PEMBEKALAN PENGETAHUAN TENTANG MOTIVASI BELAJAR DARING, MANAJEMEN WAKTU, DAN MANAJEMEN UANG SAKU BAGI SISWA SMP DAN SMA KRISTEN KALAM KUDUS - Setiyaningrum, Ari; Salim, Lina; Utami, Novia (STIE Pelita Nusantara, 2023)
The covid-19 pandemic has had an impact on almost all sectors, including education. School activities must be carried out online through distance learning. The problem faced by Kalam Kudus Christian Middle School and High School students as service partners during the Covid-19 pandemic is the decline in motivation to learn due to boredom and boredom with the routine of attending online school, students/students have so far not been able to manage their time well. more effective and unable to manage pocket money more wisely. The aim of carrying out this community service is to motivate students to study, especially online, increase students' knowledge about the importance of time management and pocket money management and their application in everyday life. Community service activities were carried out in the form of online training and involved 180 students of Kalam Kudus Christian Middle School and 133 students of Kalam Kudus Christian High School. The results of this community service activity concluded that this knowledge provision and training activity regarding online learning motivation, time management, and pocket money management was proven to be able to increase the knowledge and understanding of Kalam Kudus Christian Middle School and High School students. Keywords: learning motivation, pocket money management, pandemic covid-19, time management, students